Corrupção passiva: análise do artigo 317 do Código Penal e sua relação com as Leis n. 8.429/92, n. 9.034/95 e n. 9.613/98 - Teixeira, Juliana Ferrer (2010)
This text aims a wide-range study of the named passive corruption crime, stated on article 317 of the Brazilian Penal Code. The effective combat against passive corruption crime is a challenge faced by the State. Thereby, the law community should examine this subject in order to properly apply the law as well as to search, within the legislation, meanings to this goal. The concept of corruption, the historic origins of the legal definition, its fundaments and elements, as its description, passive and active subjects, illegal benefit/bribe, qualified and privileged figures forms, among others aspects are analyzed. The study also refers to the relation between passive corruption and other crimes against public administration stated on the Penal Code, and with crimes established outside the codified legislation. Finally, it analyses the application of the laws n. 8.429/92, n. 9.034/95 and n. 9.613/98, as an effort against public administration crimes , in special against passive corruption . By examining national and foreign doctrine and jurisprudence, this work presents as result the analysis of the article 317 s main aspects and its possible relations with the laws n. 8.429/92, n. 9.034/95 and n. 9.613/98